Increased local IgE production induced by common aeroallergens and phenotypic alteration of mast cells in Chinese eosinophilic, but not non‐eosinophilic, chronic rhinosinusitis with nasal polyps. Issue 5 (May 2014) - Cao, P.‐P.; Zhang, Y.‐N.; Liao, B.; Ma, J.; Wang, B.‐F.; Wang, H.; Zeng, M.; Liu, W.‐H.; Schleimer, R. P.; Liu, Z.
Summary Background Eosinophilic and non‐eosinophilic chronic rhinosinusitis with nasal polyps (CRSwNP) display distinct patterns of inflammation. However, the pathogenic mechanisms underlying the heterogeneity of CRSwNP need further investigation. Objective To investigate local immunoglobulin E (IgE) production and phenotype of mast cells in eosinophilic and non‐eosinophilic CRSwNP in Chinese. Methods Total and specific IgE levels were analysed by means of the ImmunoCAP system. The molecular steps involved in class‐switch recombination to IgE were investigated using RT‐PCR assays. Mast cell phenotypes, IgE‐ and high‐affinity IgE receptor (FcεRI)‐positive cells, and allergen binding to specific IgE in sinonasal mucosa were determined by means of immunohistochemistry. Results Compared with controls and non‐eosinophilic CRSwNP, local total IgE levels were increased, and local specific IgE to common aeroallergens was more frequently found, in Chinese eosinophilic CRSwNP independent of atopy and without significant association with Staphylococcus aureus enterotoxins. The ε germline gene transcript was also more frequently detected in eosinophilic CRSwNP. The number of IgE‐ and FcεRI‐positive cells was increased in eosinophilic CRSwNP. Most IgE‐ and FcεRI‐positive cells were mast cells. Dust mite antigens could bind to IgE on mast cells in situ. The number of mast cells positive for both tryptase and chymase and activated mast cells was increased in eosinophilic CRSwNP and the number of activated mast cells positively correlated with local IgE level, eotaxin‐1 level, and eosinophil count in CRSwNP. Conclusions and Clinical Relevance The local IgE induced by common aeroallergens may mediate mast cell activation and contribute to subsequent eosinophilic inflammation in Chinese CRSwNP. This study offers a rationale for considering intervention strategies designed to target 'local allergy' in eosinophilic CRSwNP.